BrightHearts: A pilot study of biofeedback assisted relaxation training for the management of chronic pain in children with cerebral palsy - Katarina Ostojic; Nicole Sharp; Simon Paget; George Khut; Angela Morrow (Wiley, 2022)
Abstract Background Chronic pain is estimated to impact one‐in‐three children with cerebral palsy (CP). Psychological interventions including behavioral and cognitive strategies play a key role in chronic pain management, but there is a paucity of research exploring their use in children with CP. Aim To investigate the acceptability and feasibility of biofeedback assisted relaxation training (BART) for chronic pain management in children with CP using a mixed‐methods study design. Methods Biofeedback assisted relaxation training was delivered via BrightHearts, an iOS application. Inclusion criteria were as follows: CP; self‐reported chronic pain; age 9‐18 years; and fluent English speaker. Children used BrightHearts for ten minutes daily, over four weeks. Qualitative post‐intervention interviews were undertaken (child, parent) and quantitative pre‐post measures (child) were gathered including pain intensity (numerical rating scale), and anxiety intensity (numerical rating scale). Content analysis was conducted for qualitative data. Descriptive statistics and exploratory analyses were performed for quantitative data. Results Ten children participated (n = 3 male, mean age = 13.1 years SD = 2.5 years, GMFCS level I = 4, II = 2, III = 3, IV = 1). Predominant movement disorder was spasticity (n = 7) and dyskinesia, mainly dystonia (n = 3). Content analysis suggested an overarching theme "BrightHearts is a good thing to put in my toolbox" providing an overall representation of participants' experiences. For many, BrightHearts was a valuable supplement to children's pain management strategies: "The source of the pain is still there, but the actual effect of the pain isn't so relevant." Four sub‐themes were identified: "Managing my pain;" "Managing my anxiety and stress," "Helping me do what I need to do;" and "Fitting it into my life." Some participants reported improvements in their anxiety management, and others described benefits in sleep and school following improved pain/anxiety management. A range of practical and personal factors within this heterogeneous group presented barriers to using BrightHearts including limited time, attention, and boredom. Seven‐out‐of‐eight children would recommend BrightHearts to others with chronic pain and six‐out‐of‐eight noticed a difference in their pain since using BrightHearts (n = 2 missing data). Non‐significant reductions in pain or anxiety intensity scores were found following the intervention. Conclusion This pilot suggests BrightHearts is an acceptable and feasible intervention for chronic pain management in children with CP and may be useful for some children as part of a multimodal approach.